The experiential perspectives of parents caring for a loved one with a restrictive eating disorder in the UK. Issue 6 (12th November 2021) - Cribben, Hannah; Macdonald, Pamela; Treasure, Janet; Cini, Erica; Nicholls, Dasha; Batchelor, Rachel; Kan, Carol
Abstract : Background: Parents of a loved one with an eating disorder report high levels of unmet needs. Research is needed to understand whether clinical guidance designed to improve the experience of parents has been effective. Aims: To establish parents' experiential perspectives of eating disorder care in the UK, compared with guidance published by Beat, a UK eating disorders charity, and Academy for Eating Disorders, the leading international eating disorders professional association. Method: A total of six focus groups (one online and five face-to-face) were held throughout the UK. A total of 32 parents attended. All participants were parents of a loved one with a diagnosis of anorexia nervosa or atypical anorexia nervosa (mean age 22 years; mean duration of illness 4.4 years). Focus groups were transcribed, and the text was analysed with an inductive approach, to identify emerging themes. Results: Four key themes were identified: (a) impact of eating disorder on one's life, (b) current service provisions, (c) navigating the transition process and (d) suggestions for improvement. Conclusions: Current experiences of parents in the UK do not align with the guidelines published by Beat and Academy of Eating Disorders. Parents identified a number of changes that healthcare providers could make, including improved information and support for parents, enhanced training of professionals, consistent care across all UK service providers, policy changes and greater involvement of families in their loved one's care. Findings from this project informed the design of a national web-survey on loved ones' experience of care in eating disorders.